2013
DOI: 10.1038/ncomms3952
|View full text |Cite
|
Sign up to set email alerts
|

A general approach to crystalline and monomodal pore size mesoporous materials

Abstract: Mesoporous oxides attract a great deal of interest in many fields, including energy, catalysis and separation, because of their tunable structural properties such as surface area, pore volume and size, and nanocrystalline walls. Here we report thermally stable, crystalline, thermally controlled monomodal pore size mesoporous materials. Generation of such materials involves the use of inverse micelles, elimination of solvent effects, minimizing the effect of water content and controlling the condensation of ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
298
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 230 publications
(306 citation statements)
references
References 34 publications
8
298
0
Order By: Relevance
“…For instance, Fan et al prepared multicomponent mesoporous metal oxides in a versatile sol-gel solution consisting of acetic acid 13 . Suib et al reported an inverse micelle synthesis system to prepare mesoporous metal oxides 14 . Mesoporous materials with diverse morphologies and tunable pore sizes have been prepared by controlling the synthesis conditions and the properties of the template molecules based on soft templating 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Fan et al prepared multicomponent mesoporous metal oxides in a versatile sol-gel solution consisting of acetic acid 13 . Suib et al reported an inverse micelle synthesis system to prepare mesoporous metal oxides 14 . Mesoporous materials with diverse morphologies and tunable pore sizes have been prepared by controlling the synthesis conditions and the properties of the template molecules based on soft templating 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…16,17,20 No small surfactant soft-templating method exists for the synthesis of mesoporous metal titanates in the literature. 16 Also note that the metal titanates form at high temperatures (250−350°C).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The resulting aggregated nanoparticles exhibit tunable pore structures, excellent thermal stability, and easily accessible oxidation states which contribute to a wide range of organic catalytic transformations [1]. Among the variety of transition metal oxide systems, mesoporous manganese oxides have proven to be efficient catalysts in the oxidation of alcohols to carboxylic acids.…”
mentioning
confidence: 99%